Dynamic capabilities, Marketing Capability and Organizational Performance - Takahashi, Adriana Roseli Wünsch (2017)
The goal of the study is to investigate the influence of dynamic capabilities on organizational performance and the role of marketing capabilities as a mediator in this relationship in the context of private HEIs in Brazil. As a research method we carried out a survey with 316 IES and data analysis was operationalized with the technique of structural equation modeling. The results indicate that the dynamic capabilities have influence on organizational performance only when mediated by marketing ability. The marketing capability has an important role in the survival, growth and renewal on educational services offerings for HEIs in private sector, and consequently in organizational performance. It is also demonstrated that mediated relationship is more intense for HEI with up to 3,000 students and other organizational profile variables such as amount of courses, the constitution, the type of institution and type of education do not significantly alter the results.